Association of Low-Dose Aspirin and Survival of Women With Endometrial Cancer. Issue 1 (July 2016) - Matsuo, Koji; Cahoon, Sigita S.; Yoshihara, Kosuke; Shida, Masako; Kakuda, Mamoru; Adachi, Sosuke; Moeini, Aida; Machida, Hiroko; Garcia-Sayre, Jocelyn; Ueda, Yutaka; Enomoto, Takayuki; Mikami, Mikio; et al.
Abstract : OBJECTIVE: To examine the survival outcomes in women with endometrial cancer who were taking low-dose aspirin (81–100 mg/d). METHODS: A multicenter retrospective study was conducted examining patients with stage I–IV endometrial cancer who underwent hysterectomy-based surgical staging between January 2000 and December 2013 (N=1, 687). Patient demographics, medical comorbidities, medication types, tumor characteristics, and treatment patterns were correlated to survival outcomes. A Cox proportional hazard regression model was used to estimate adjusted hazard ratio for disease-free and disease-specific overall survival. RESULTS: One hundred fifty-eight patients (9.4%, 95% confidence interval [CI] 8.8–11.9) were taking low-dose aspirin. Median follow-up time for the study cohort was 31.5 months. One hundred twenty-seven patients (7.5%) died of endometrial cancer. Low-dose aspirin use was significantly correlated with concurrent obesity, hypertension, diabetes mellitus, and hypercholesterolemia (all P <.001). Low-dose aspirin users were more likely to take other antihypertensive, antiglycemic, and anticholesterol agents (all P <.05). Low-dose aspirin use was not associated with histologic subtype, tumor grade, nodal metastasis, or cancer stage (all P >.05). On multivariable analysis, low-dose aspirin use remained an independent prognostic factor associated with an improved 5-year disease-free survival rate (90.6% compared with 80.9%, adjusted hazard ratio 0.46, 95% CI 0.25–0.86, P =.014) and disease-specific overall survival rate (96.4% compared with 87.3%, adjusted hazard ratio 0.23, 95% CI 0.08–0.64, P =.005). The increased survival effect noted with low-dose aspirin use was greatest in patients whose age was younger than 60 years (5-year disease-free survival rates, 93.9% compared with 84.0%, P =.013), body mass index was 30 or greater (92.2% compared with 81.4%, P =.027), who had type I cancer (96.5% compared with 88.6%, P =.029), and who received postoperative whole pelvic radiotherapy (88.2% compared with 61.5%, P =.014). These four factors remained significant for disease-specific overall survival (all P <.05). CONCLUSION: Our results suggest that low-dose aspirin use is associated with improved survival outcomes in women with endometrial cancer, especially in those who are young, obese, with low-grade disease, and who receive postoperative radiotherapy. Abstract : Supplemental Digital Content is Available in the Text.Low-dose aspirin use is associated with improved survival of women with endometrial cancer, especially the obesity-related cancer type.